The role of shopping in human life in 2021 - Samek, Ilona; Jańczyk, Magdalena; Milanowska, Joanna (Journal of Education, Health and Sport, 2021)
Introduction: Society today is overly overwhelmed with advertisements for attractive products and ways to purchase them. The population is becoming richer and richer, which means they can spend more money on entertainment and their own pleasures. Purpose: To present the role of shopping in human life in 2021 from the perspective of consumers. Material and method: The study was carried out using the author's questionnaire. 260 questionnaires were collected and analyzed. Results: Men (52.3%) and women (47.7%) participated in the study. More than half of them (53.8%) were employed and more than 30% were studying. One in three respondents earned cash income greater than the minimum national gross rate. Nearly 60% rated their material situation as good. The analysis showed knowledge of the term "consumerism" by 83.1% of people. The study showed that the respondents shopped several times a week (69.2%) and even daily (18.5%). In order to buy food products, they usually visited supermarkets (64.6%), and in buying products they were most often guided by quality (47.7%). They are most encouraged by sales (50.8%), as well as recommendations from friends (18.5%) and product ingredients (12.6%). The data shows that as many as 58.5% of respondents used shopping to improve their mood. They were also induced to buy products by advertisements in the media (49.2%). Conclusions: For consumers, apart from the price, the quality of the products is of primary importance. They buy mainly in large supermarkets and via the Internet. The advertisements in media, promotions and the desire to improve one’s mood are the reasons of increasing phenomenon of consumerism.